Firearm injury—a preventable public health issue. (November 2022) - Patel, Jay; Leach-Kemon, Katherine; Curry, Gwenetta; Naghavi, Mohsen; Sridhar, Devi
Summary: Firearm-related injury is a leading cause of death disproportionately affecting adolescents and young adults across the world, especially in the Americas. Little progress has been made over the past four decades, as inaction and the adoption of ineffective or unevidenced interventions have become commonplace. The COVID-19 pandemic reconfigured health systems towards prevention and harm reduction, sharpened public attention to the burden of preventable deaths, and inspired a fresh ambition of eliminating avertable deaths. In this Viewpoint, we argue that preventing firearm injury should garner bolder action in post-pandemic public health and we present a case for reducing the global burden of firearm injury supported by evidence and international examples. Crucially, we aim to guide policy making in directions that end the cycle of grief, anger, activism, deflection, and inaction and create more peaceful and fairer societies.